What Happens When Econometrics and Psychometrics Collide? An Example Using the PISA Data - John Jerrim; Luis Alejandro Lopez-Agudo; Oscar D. Marcenaro-Gutierrez; Dominique Shure (Institute of Labor Economics (IZA), 2017)
International large-scale assessments such as PISA are increasingly being used to benchmark the academic performance of young people across the world. Yet many of the technicalities underpinning these datasets are misunderstood by applied researchers, who sometimes fail to take their complex sample and test designs into account. The aim of this paper is to generate a better understanding amongst economists about how such databases are created, and what this implies for the empirical methodologies one should (or should not) apply. We explain how some of the modelling strategies preferred by economists seem to be at odds with the complex test design, and provide clear advice on the types of robustness tests that are therefore needed when analyzing these datasets. In doing so, we hope to generate a better understanding of international large-scale education databases, and promote better practice in their use.
Keywords: I20; C18; C10; C55; 330; sample design; test design; PISA; weights; replicate weights; plausible values